Understanding the mechanisms underlying the socioeconomic disparities in cancer screening among Australian women - Larry Myers; Nicole Perry; Laura Anderson; Michael Ireland; Claire Nightingale; Belinda Goodwin (BMC Public Health)
Abstract Background Little is known about individual, as opposed to area-level, variance in socioeconomic status (SES) and how this impacts screening participation. This study explores potential mechanisms underlying the relationship between SES and cancer screening amongst women eligible for breast, cervical, and bowel cancer screening. Methods Australian women aged 50–74 years (N = 874) took part in an online survey examining participants’ health and cancer screening behaviours. Relationships between individual and area-level SES, cancer screening participation, stress, general self-efficacy, and screening literacy were examined using structural equation modelling. Frequency of cancer screening barriers were calculated for each cancer type and compared for SES categories. Results The structural equation model including stress and screening literacy as mediators yielded excellent fit, χ2 (26) = 33.322, p = .153, TLI = 0.992. Lower individual level SES was associated with higher stress and lower screening literacy. Higher stress was related to lower screening participation in all three programs, and lower screening literacy was associated with low cervical and breast cancer screening. The only significant relationship between area-level SES and screening participation was with participation in cervical screening. All indirect effects between area level SES and screening were non-significant. The types of barriers reported for each cancer screening type were similar between high and low socioeconomic individuals. In all three screening programs, intending to participate in cancer screening but not getting around to it, and not liking the screening method were commonly reported reasons for non-participation. Conclusions This study is the first to investigate the effects of individual level SES on cancer screening in Australia and one of the few studies to examine underlying mechanisms simultaneously across various screening programs. Reducing stress and improving screening literacy may help to improve cancer screening participation among low SES individuals. Our results also suggest that tailoring interventions to the SES background of women may not enhance their effectiveness. Interventions aiming to reduce the SES screening disparities may achieve more success through addressing underlying mechanisms as opposed to the behavioural barriers themselves.